Policy commitment, legal and regulatory framework, and institutional support for PPP in international comparison: Indexing countries' readiness for taking up PPP - Koen Verhoest; Ole Helby Petersen; Walter Scherrer; Raden Murwantara Soecipto (University of Salzburg, Department of Social Sciences and Economics, 2014)
In this paper we develop an index of the governmental support for PPP - a 'PPP Governmental Support Index' - which aims to measure the extent to which national governments provide an institutional framework that is either conducive or preventive for the introduction and diffusion of PPPs within infrastructure. First, based on a substantive review of the literature we define the elements of the PPP Governmental Support Index, including the policy and political commitment regarding PPPs, the legal and regulatory framework regarding PPPs, as well as the presence/absence of PPP-supporting structures and instruments (PPP-units, procedures for project appraisal and green lightning, and standardization of instruments and contracts). Second, we calculate the 'PPP Governmental Support'-index for 15 European countries, cluster them and compare similarities and differences in national institutional support of PPPs. Third, we present a first and preliminary exploration of a potential link between national institutional index scores and the number and capital value of implemented PPP projects. Lastly, we discuss the potential and usefulness as well as methodological limitations of the presented PPP Governmental Support Index and elaborate on how this index might be utilized to strengthen future comparative PPP research.
Keywords: L32; 330; Public-private partnerships; comparative index; country rankings; institutional framework; COST Action TU1001